PENGARUH POLITIK TERHADAP HUKUM - Puji Kurniawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
Islam is the last religion of Allah SWT and the religion that was conveyed to the prophet Muhammad SAW through the angel Gabriel with the aim to change the human nature towards a better side by Allah SWT. Many ways are done by humans to achieve piety at His side or what is also called